2006
DOI: 10.1055/s-2006-955085
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Differently Affects Osteoblast Differentiation Depending upon its Differentiation Stage

Abstract: Smad3, a critical component of the TGF-beta signaling pathways, plays an important role in the regulation of bone formation. However, how Smad3 affects osteoblast at the different differentiation stage remains still unknown. In the present study, we examined the effects of Smad3 on osteoblast phenotype by employing mouse bone marrow ST-2 cells and mouse osteoblastic MC3T3-E1 cells at the different differentiation stage. Smad3 overexpression significantly inhibited bone morphogenetic protein-2 (BMP-2)-induced A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…9) On the other hand, TGF-β1 blocked osteogenesis by a variety of mechanisms depending on cell density, TGF-β1 concentration and differentiation stage of the cells. [10][11][12] TGF-β1 also blocked odontogenesis by downregulation of dentin sialophosphoprotein. 13) The mitogen-activated protein kinase (MAPK) pathway has been proposed to negatively regulate Smad pathway and osteoblast mineralization.…”
Section: Introductionmentioning
confidence: 92%
“…9) On the other hand, TGF-β1 blocked osteogenesis by a variety of mechanisms depending on cell density, TGF-β1 concentration and differentiation stage of the cells. [10][11][12] TGF-β1 also blocked odontogenesis by downregulation of dentin sialophosphoprotein. 13) The mitogen-activated protein kinase (MAPK) pathway has been proposed to negatively regulate Smad pathway and osteoblast mineralization.…”
Section: Introductionmentioning
confidence: 92%
“…cDNA synthesis, reverse transcription, and PCR were performed as previously described [49]. The amplified DNA was separated on 2% agarose gels and stained with ethidium bromide.…”
Section: Rna Extraction and Semi-quantitative Rt-pcrmentioning
confidence: 99%
“…We showed previously that Smad3, a crucial TGF-␤-signaling molecule, promotes alkaline phosphatase (ALP) activity in mouse osteoblastic MC3T3-E1 cells (5,6), and Borton et al (7) have found that mice with targeted disruption of Smad3 exhibit osteopenia caused by decreased bone formation, suggesting that the Smad3 molecule is a promoter of bone formation. Moreover, we demonstrated that TGF-␤-responsive ERK1/2 and c-Jun N-terminal kinase (JNK) cascades negatively regulate Smad3-induced transcriptional activity and ALP activity in osteoblasts (8).…”
mentioning
confidence: 99%